Mixed Bag of Interstitial Lung Diseases at Tertiary Care Centre - D. Shah, Arti; Malani, Swati; Swati, Amrita; V. Shah, Kusum (International Journal of Psychosocial Rehabilitation, 2020)
Context: ILD or DPLD is a heterogeneous group of disorders that is characterized by varying degrees of inflammation and fibrosis in the lung parenchyma. This study is being done to analyze the spectrum of ILD, their common clinical presentations, radiological features, and causes so that it may help in a better understanding of the disease in the Indian context. Aims: To study the underlying causes of ILD in patient diagnosis based on clinical history & HRCT. Settings and Design: We conducted a retrospective study based on the available departmental data records of 41 ILD patients from October 2017 to October 2019 at our tertiary care center. Methods and Material: Patients with chief complaints of dyspnea and cough with a chest radiograph and HRCT thorax suggestive of ILD were collected for the study, and statistical analysis was done. Statistical analysis used: SPSS computer software version 20.0. Results: Forty-one patients were enrolled. The mean age of presentation was 55.75 years. There was male predominance seen. Progressive dyspnea (90.24%) and dry cough (63.4%) were the most common symptoms in ILD patients. On examination, Velcro crackles, clubbing, & restrictive pattern on spirometry were predominantly found. IPF was the most common (46.43%) ILD, followed by non-IPF IIPs, connective tissue disease-related ILD, chronic HP, sarcoidosis, and smoking-related ILD, which were diagnosed in 19.51%, 17.07%, 7.32%, 7.32%, and 2.44% of the subjects, respectively. Conclusions: IPF was the most common IIP found, followed by NSIP. CTD & chronic HP were found as definitive causes in some, which changed the treatment & prognosis.